Driving under the influence (DUI) detection system / Muhammad Dzikri Faizal - Faizal, Muhammad Dzikri (2024)
The "Driving Under the Influence (DUI) Detection System" project aims to address the alarming rate of accidents caused by drunk drivers in Malaysia, exacerbated by the insufficient enforcement of laws pertaining to impaired driving. Focusing on enhancing road safety, this project addresses the serious problem of drunk driving by developing a prototype for a Driving Under the Influence detection system. The system utilizes an Arduino-Uno as microcontroller, MQ3 and IR sensors for input, and LCD, LED, and Buzzer for output. Arduino IDE is employed for coding, while Proteus 8 Professional is used for circuit and PCB design. Hardware components include MQ3 and IR sensors for alcohol and driver presence detection, respectively, and output is managed through LCD, LED, and Buzzer, with communication facilitated by a GSM module. The expected outcomes encompass successful detection of alcohol presence, accurate identification of the driver's presence, SMS notifications through the GSM module, and seamless functioning of LCD, LED, and Buzzer for effective feedback.